Sustainable cellulose nanofiber extraction from Borassus flabellifer: a comprehensive study and analytical insights - Surya, S.; Soman, Arathy; Krishnan, Akhil; Suresh, M. Parvana; Neenu, K. V.; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; Begum, P. M. Sabura; Dominic, C. D. Midhun (Biomass Conversion and Biorefinery, 2025)
Cellulose, a biodegradable and renewable material, is versatile and transforms various fields. This work uses a chemo-mechanical method to discuss the extraction and analysis of palmyra (Borassus flabellifer) fruit derived cellulose nanofibers (PFCNF). The mild acid treatment, steam explosion, and homogenization could increase the physico-chemical properties of Borassus flabellifer fiber. The chemical composition and FTIR analysis confirmed the successful elimination of the hemicellulose, lignin, and other extractives in the palmyra fruit pulp. The solid-state 13C NMR proved the cellulose type I structure of the extracted PFCNF. The crystallinity index of PFCNF was found to be 57%. The yield of the cellulose was calculated to be 44%. PFCNF exhibited fibrous morphology with a nanodimension of 10-80 nm, validated using scanning electron microscopy and transmission electron microscopy. With progressive treatments, the thermal stability was increased, and the Tmax of PFCNF was 32 degrees C higher compared to the raw fibers. These superior properties further support their potential in eco-friendly packaging, advanced composites, biomedical materials, film production, electronics, coating materials, and paper production.
Keywords: Borassus flabellifer; Biomass; Cellulose nanofiber; Eco-friendly extraction; Sustainable materials; Waste valorization

Sustainable isolation of cellulose nanofibers with superior crystallinity and thermal stability from Terminalia catappa L. fruit peel waste - Harsha, R.; Mol, A. P. Princy; Paul, Sharon; Badawi, Michael; Ajithkumar, T. G.; Rao, H. Jeevan; Parameswaranpillai, Jyotishkumar; Nair, Ajalesh B.; Begum, P. M. Sabura; Dominic, C. D. Midhun (Biomass Conversion and Biorefinery, 2025)
Turning agricultural waste into value-added products is a key focus of sustainable development. Herein, cellulose nanofibers (CNF) were extracted from the pericarp of Terminalia catappa L. for the first time. The CNF was extracted by chlorine-free pretreatment methods followed by oxalic acid hydrolysis (5 wt%) assisted with steam explosion. The prepared CNF were characterized by Fourier transform infrared spectroscopy (FTIR), solid-state 13C nuclear magnetic resonance spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA and DTG). FTIR analysis confirmed the successful removal of lignin and hemicellulose during chemical treatment which was again validated by solid-state 13C NMR analysis. TEM image revealed that the diameter of the extracted nanofibers ranges from 14 to 18 nm. From XRD analysis, the crystallinity index of the CNF was 82%, while that of the raw sample was 62 %. The temperature at which the maximum degradation (Tmax) of CNF occurred was found to be 372 degrees C which is superior to that of the raw sample (334 degrees C). The extracted cellulose nanofibers were used to prepare cellulose paper, demonstrating a tensile strength of 1.1 MPa, indicating its potential suitability for biodegradable packaging applications.
Keywords: cellulose; Cellulose nanofiber; green synthesis; Waste to wealth

Sustainable nanocellulose extraction from salacca zalacca peel using chlorine-free and low-acid treatments - Krishnan, Akhil; Paul, Sharon; Phiri, Resego; Srisuk, Rapeeporn; Kumar Singh, Manoj; Palaniappan, Sathish Kumar; Rangappa, Sanjay Mavinkere; Dominic, C. D. Midhun; Ajithkumar, Thalasseril G.; Siengchin, Suchart (ACS Omega, 2026)
Conversion of agro-waste to value-added products is one of the important principles of a green circular economy. A novel sustainable technique has been reported by using chlorine-free extraction of cellulose nanofibers (CNFs) from the peels of Salacca zalacca, a common fruit found in Asia. The fruit peels were exposed to alkali treatment using 2% NaOH (60 degrees C, 2 h), chlorine-free bleaching using 15% hydrogen peroxide (60 degrees C, 2 h), and sulfuric acid hydrolysis (15% v/v) for the extraction of CNFs. Various analytical methods were employed to characterize the prepared CNFs. The Fourier transform infrared spectroscopy (FTIR) and 13C solid state nuclear magnetic resonance (NMR) spectra showed the complete elimination of lignin and hemicellulose in the prepared CNFs. The elemental composition and high purity of CNFs were further verified by energy-dispersive X-ray analysis (EDX). The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images proved the fibrous morphology of the prepared CNFs, and the diameters of the cellulose nanofibers were found to be 15-30 nm. The X-ray diffraction (XRD) studies disclosed the type-I cellulosic structure in the prepared CNFs with a high crystallinity index (73%). The thermogravimetric analysis (TGA) demonstrated the superior thermal stability of the prepared CNFs (T max is 350 degrees C) compared to the raw fiber (T max is 320 degrees C). Based on the obtained results, it has been explored that the extracted highly pure CNFs can be used for fabricating bionanocomposites for high performance applications, including food packaging, sensors, water treatment, green tires, etc.